PARIWISATA KREATIF BERBASIS INDUSTRI BATIK SEBAGAI UPAYA PENGEMBANGAN EKONOMI LOKAL KOTA PEKALONGAN - L Latifah; Maya Damayanti (TATALOKA, 2016)
Currently, Pekalongan City is known as the city of batik. The recognition is both at national and international levels whereas Pekalongan has been acknowledged as a world creative city based on the art and culture of batik. Batik is an essential commodity in Indonesian creative industries and has been the major commodity of Pekalongan. Batik industry is also capable of creating an inter-business association like the canting making business and fabric dyes business. As a city of batik, Pekalongan is prepared as a tourist destination through the availability of Batik Museum and two centers of batik craftsmen. The attraction has been increasing because tourists do not only see the process but can practice on how to make batik along with the batik craftsmen and interact with the related tools and materials, and this is known as creative tourism. The impact of the creative tourism can become one of the efforts to the local economic development of Pekalongan because it has been able to make linkages between sectors in tourism and batik industry.